Naturally low biodiversity is getting a raw deal in the media - Procheş, Şerban (Frontiers in Conservation Science, 2022)
While media usage has helped biodiversity gain a central spot in the contemporary conservation landscape, it is acknowledged that high biodiversity in itself is not always the best indication of conservation value. There are multiple reasons why low-biodiversity systems have to be valued. Such systems are easier to appreciate by the general public in their entirety, and also easier to study, with most model systems referring to low numbers of species. In remote and environmentally harsh settings, biodiversity can increase via biological invasion, which is usually perceived as a negative anthropogenic impact. Island systems, typically lower in biodiversity compared to continental settings, are, specifically thanks to the available niche space, laboratories of speciation and potentially macroevolutionary innovation. Although biodiversity hotspots are at the centre of global conservation efforts, coldspots have their own dynamics and conservation needs, generally poorly understood at this stage due to the high-biodiversity focus. Here, I discuss the media relevance and, where relevant, distortion, of these aspects. I conclude by recommending a local rather than global focus in the marketing of conservation, which could encourage an appreciation of naturally low biodiversity.